A subtle war of words on the internet. (10th October 2008) - Saunders, Carol S.; Flammia, Madelyn
As people of many cultures do business with one another, they often struggle to find a common language. Or do they? English is typically considered not only the language of business, but also the language of the internet. But will its dominance continue as more Chinese start using the internet. The subtle and not so subtle implications of being a dominating language, be it English or Chinese, are discussed.